Potential impact of relational job design on future intentions of episodic volunteers in major sport events - Su, Jingxuan; Li, Haifeng; Ma, Hongyu (Frontiers in Psychology, 2024)
Introduction Based on Social Identity Theory, this study hypothesized the parallel mediating roles of organizational commitment, and commitment to beneficiaries, in the relationship between relational job design and future volunteer intentions among episodic volunteers at a mega sport event. Perceived organizational support was tested as a moderator of this relationship. Methods Participants were 617 episodic volunteers (35.7% male and 64.3% female) at the 7th CISM Military World Games in Wuhan, China, who completed online questionnaires. Results Regression-based analyses indicated that relational job design positively predicted future volunteer intentions through organizational commitment. Although the results did not indicate a mediating role of commitment to beneficiaries, relational job design was still shown to positively predict commitment to beneficiaries. Furthermore, the association between relational job design and commitment to beneficiaries was moderated by perceived organizational support, such the effect was stronger when perceived organizational support was high. Discussion The results have practical implications for strengthening episodic volunteers’ intentions to participate in future mega sport events, creating a legacy of volunteerism.